The Novel Structural Protein of Human Cytomegalovirus, pUL25, Is Localized in the Viral Tegument - Zini, N. (American Society for Microbiology, 1999)
Human cytomegalovirus UL25 codes for a structural phosphoprotein of 85 kDa (C. J. Baldick and T. Shenk, J. Virol. 70:6097–6105, 1996; M. C. Battista et al., J. Virol. 73:3800–3809, 1999). In this study we analyzed the intracellular and intraviral localization of pUL25 by confocal and immunoelectron microscopy and found that pUL25 is a component of the viral tegument and the dense body matrix, acquired during the late cytoplasmic phase of virus maturation.